A Role and Essence of the Strategic Potential ("Journal "U". Economy. Management. Finance.", 2017)
This article is devoted to the analysis of a role and essence of strategic potential in entity's activities. The main aspects of strategic potential are considered in the work. Topicality of this subject is indisputable as strategic potential is one of key aspects of successful performance of the company.
Keywords: strategic potential; marketing